Atherosclerotic cardiovascular disease landscape in Singapore - Sia, Ching-Hui; Simon, Oliver; Loh, Poay-Huan; Poh, Kian Keong (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular disease (CVD) is the leading cause of death worldwide, accounting for over one-third of all deaths in Singapore. An analysis of age-standardized mortality rates (ASMR) for CVD in Singapore revealed a deceleration in the initial rapid decline in ASMR. A decrease in smoking prevalence may have contributed to the initial rapid decline in ASMR. Furthermore, other major risk factors, such as diabetes mellitus, hypertension, elevated low-density lipoprotein levels, and obesity, are steadily rising. Singapore's CVD economic burden is estimated to be 8.1 billion USD (11.5 billion SGD). The burden of CVD can only be reduced using individual and population-based approaches. Prevention programs must also be developed based on an understanding of risk trends. Therefore, this article attempts to capture the burden of CVD, trends in risk factor control, preventive care, disparities, and current unmet needs, particularly in atherosclerotic cardiovascular disease management in Singapore.